Photoinduced birefringence at low temperatures in Langmuir-Blodgett films of azobenzene-functionalized copolymers - Silva, JR; Dall'Agnol, F. F.; De Souza, N. C.; Oliveira, O. N.; Giacometti, J. A. (Elsevier B.V., 2003)
The temperature dependence has been investigated for the photoinduced birefringence in Langmuir-Blodgett (LB) films from the azocopolymer 4-[N- ethyl -N-(2-hydroxyethyl)] amino-2'-chloro-4'-nitroazobenzene (MMA-DR13) mixed with cadmium stearate. The buildup and relaxation of the birefringence in the range from 20 to 296 K were fitted with a Kohlrausch-Williams-Watts (KWW) function, with a beta-value of 0.78-0.98 for the build-up and 0.18-0.27 for the decay. This is consistent with a distribution of time constants for the kinetics of the birefringence processes. The maximum birefringence increased with increasing temperature up to 120 K because the free volume fluctuation also increased with temperature. Above 120 K, the birefringence decreased with temperature as thermal diffusion dominates. In the latter range of temperature, an Arrhenius behavior is inferred for both build-up and decay of birefringence. In each case two activation energies were obtained: 0.8 and 5 kJ/mol for the build-up and 10 and 30 kJ/mol for the decay. The energies for the build-up are much lower than those associated with motion of the polymer chain, which means that the dynamics is governed by the orientation of the chromophores. For the decay, local motion of lateral groups of the polymer chains becomes important as the activation energies are within the range of gamma-relaxation energies. (C) 2003 Elsevier B.V. B.V. All rights reserved.
Keywords: Langmuir-Blodgett techniques; special-purpose functionalized conjugated polymers